THE IMPLEMENTATION OF RUNNING DICTATION TECHNIQUE TO IMPROVE STUDENT’S LISTENING SKILLS - Handy Hidayati; Fatkurochman, Henri; Oktarini, Widya (ENJEL: English Journal of Education and Literature, 2023)
Running dictation is one part of dictation. In addition, running dictation is a game in learning where students are divided into several groups to dictate several sentences. There are runners and writers for each group (usually each group consists of five or more people). Every teacher needs a strategy or technique to achieve a lesson in the teaching-learning process. So, the researcher was chosen running dictation as a learning technique in this research. The purpose of this research is to implement running dictation in learning to improve student’s listening skills and to test student’s improvement in listening using running dictation. To collect the data, the researcher observed student’s activities and gave pre-test and post-test tests using a Classroom Action Research design or CAR. In this study, there were two cycles, and in each cycle, there were two meetings. The result after implementing the action in cycle one and cycle two, it was proven that the running dictation technique was able to improve student’s listening skills of class XB students of SMA Muhammadiyah 2 Wuluhan in the academic year 2022/2023.